1993
DOI: 10.1007/bf00012527
|View full text |Cite
|
Sign up to set email alerts
|

Soybean response to nodulation by rhizobitoxine-producing bradyrhizobia as influenced by nitrate application

Abstract: Foliar chlorosis of soybean (Glycine max [L.] Merr.) resulting from nodulation by rhizobitoxineproducing (RT +) strains of Bradyrhizobium japonicum is commonly less severe in the field than under greenhouse conditions. Differences in nutritional conditions between the field and greenhouse may contribute to this phenomenon. In particular, field-grown plants obtain some N from soil sources, whereas in the greenhouse soybean is often grown in low-N rooting media to emphasize symbiotic responses. Therefore, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Certain soybean genotypes possess the Rj4 gene, which has been shown to interdict nodulation by B. elkanii (Devine et al, 1990), but no evidence of this interdiction was observed for the cultivars included in this study. Reasons for the lack of correlation between the greenhouse and field studies for some cultivars are not known, but may include differences in plant growth stage at sampling, contrasting nutrient regimes between the greenhouse and field (Johnson et al, 1958;Teaney and Fuhrmann, 1993), and possible modifying effects of altered nodule functioning over time for the various cultivars examined (Teaney and Fuhrmann, 1992). Nevertheless, the high apparent sensitivity of many soybean cultivars to RT+ strains, combined with the high numbers of RT+ soybean bradyrhizobia present in many soils of the mid-Atlantic and southeastern USA (Caldwell and Hartwig, 1970;Fuhrmann, 1990;Keyser et al, 1984;Mpepereki and Wollum, 1991;Weber et al, 1989), justifies additional studies of the role of rhizobitoxine in the soybean-bradyrhizobia symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Certain soybean genotypes possess the Rj4 gene, which has been shown to interdict nodulation by B. elkanii (Devine et al, 1990), but no evidence of this interdiction was observed for the cultivars included in this study. Reasons for the lack of correlation between the greenhouse and field studies for some cultivars are not known, but may include differences in plant growth stage at sampling, contrasting nutrient regimes between the greenhouse and field (Johnson et al, 1958;Teaney and Fuhrmann, 1993), and possible modifying effects of altered nodule functioning over time for the various cultivars examined (Teaney and Fuhrmann, 1992). Nevertheless, the high apparent sensitivity of many soybean cultivars to RT+ strains, combined with the high numbers of RT+ soybean bradyrhizobia present in many soils of the mid-Atlantic and southeastern USA (Caldwell and Hartwig, 1970;Fuhrmann, 1990;Keyser et al, 1984;Mpepereki and Wollum, 1991;Weber et al, 1989), justifies additional studies of the role of rhizobitoxine in the soybean-bradyrhizobia symbiosis.…”
Section: Discussionmentioning
confidence: 99%